PENGARUH BUDAYA KOREA DAN TINGKAT PENDAPATAN TERHADAP MINAT BELI KONSUMEN DI WILAYAH CIKARANG - Taufik Hidayat; Nur Ekhsan; Muhammad Kosim; Asral (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to examine the influence of Korean culture and income levels on consumer buying interest in the Cikarang sub-district, West Java. The independent variables of this research are Korean culture and income level. As for the dependent variable itself is consumer buying interest. The method used in this study is to use a survey method by providing a number of questions in the form of questionnaires to the public or consumers in the Cikarang area, West Java. Determination of the sample using the probability sampling method or random sampling and then the data that has been collected was analyzed using the IBM SPSS statistics program version 22. The number of samples in this study were 100 respondents from the entire population by distributing questionnaires. The results of this study indicate that Korean culture has no effect on consumer buying interest, while the level of income has a positive effect on consumer buying interest